Functionality of special beer processes and potential health benefits - Salanță, Liana Claudia (2021)
Consumers’ demand for functional fermented food that can fulfill nutritional needs and help maintain a balanced diet while also having a positive impact on one’s health status is increasing all over the world. Thus, healthy choices could include beverages with nutrients and bioactive compounds which can be used as an effective disease-prevention strategy. Regular beer has certain health benefits which inspire further research with the prospect of obtaining special functional beers with little or no alcohol content. As observed, the special beer market remains highly dynamic and is predicted to expand even further. Therefore, brewers need to keep up with the consumers’ interests and needs while designing special beers, namely nonalcoholic beers (NABs), low-alcohol beers (LABs), and craft beers (CBs). Thus, understanding the potential uses of bioactive compounds in special beer, the wide range of therapeutic effects, and the possible mechanisms of action is essential for developing healthier beverages. This review aimed to evaluate the nutritional features of special beers, and their proven or potential beneficial actions on one’s health status and in preventing certain diseases.